High performance lithium-manganese-rich cathode material with reduced impurities. (January 2017) - Wang, Zhong; Yin, Yanping; Ren, Yang; Wang, Zhenyao; Gao, Min; Ma, Tianyuan; Zhuang, Weidong; Lu, Shigang; Fan, Ailing; Amine, Khalil; Chen, Zonghai
Abstract: Lithium-manganese-rich transition metal oxides have attracted substantial R&D attention due to their potential for high energy-density lithium-ion batteries. In this work, in situ high-energy X-ray diffraction was deployed to investigate the phase evolution during the solid-state synthesis of Li[Li0.2 Mn0.54 Ni0.13 Co0.13 ]O2 . A step-wise consumption of the starting materials was observed during the one-step heating process primarily due to the heterogeneous nature of the precursor. According to observations from in situ high-energy X-ray diffraction, a two-step process was adopted to minimize the elemental heterogeneity of the final product. The electrochemical characterization results showed a substantial improvement on the reversible specific capacity for the material synthesized through the two-step process. Graphical abstract: Highlights: Solid-state synthesis of Lithium-manganese-rich cathode is investigated by in situ XRD. Covariance analysis and Rietveld refinement are used to analyze the HEXRD data. A two-step process was adopted to minimize the elemental heterogeneity of the final product. A substantial improvement on the reversible specific capacity for the material synthesized through the two-step process.